PERJANJIAN PO BUS DENGAN PIHAK RUMAH MAKAN BAREH SOLOK KOTA SOLOK MENURUT FIKIH MUAMALAH (Studi Kasus Di Kota Solok Kabupaten Solok) - Riski Fajri; Afrian Raus (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
The The subject matter of this research is how the practice of agreement between PO and Bareh Solok Restaurant in Solok City and how the Muamalah Jurisprudence Review of the Practice of PO Agreement with Bareh Solok Restaurant in Solok City. While the purpose of this study is to find out how the practice of agreements between PO and Bareh Solok Restaurant in Solok City and to find out how the Muamalah Jurisprudence Review of the Practice of PO Agreements with Bareh Solok Restaurant in Solok City. This type of research is field research which is descriptive in nature with a qualitative approach, namely research that uses events and phenomena that occur in the field. As a primary data source, namely direct interviews with the owner of the houseamakanbarehsolok and PO Bus, while secondary data sources are books, journals, research results related to the author's study. The data collection technique used in this research is interview. Data analysis techniques with trigulation. The results of this study are how the practice of the agreement between PO and Bareh Solok Restaurant in Solok City. The practice of this agreement is that the five Po Buses came to the bareh solok restaurant to be able to do this cooperation. This agreement is not written, it is only done verbally, where this bus PO offers the bareh solok makn house for the driver and driver to eat at the restaurant and drink for free because he brings passengers who eat there. Many of these buses carry many passengers who eat there. So the restaurant agreed to an agreement whereby the restaurant provided tables for the drivers and crew to eat sopi. The driver who eats there is free but is taken from the passengers who eat there. The normal price of one person eating there is Rp. 15,000 but passengers from this bus cost Rp. 20,000 while the Muamalah Jurisprudence Review of the Practice of PO Agreement with Bareh Solok Restaurant, Solok CityThis review is based on the author's analysis that this agreement is in accordance with muamalah fiqh because in surah an-nisa verse 29, this restaurant is willing or consensual between the PO bus and the restaurant because this is one form of promotion from the restaurant, many buses that bring passengers also earn from this restaurant.